Laserlike emission from silica inverse opals infiltrated with rhodamine 6G - Alencar, MARC; Maciel, G. S.; de Araujo, C. B.; Bertholdo, R.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Elsevier B.V., 2005)
Monodisperse latex spheres were obtained by a surfactant free styrene polymerization method and used to obtain colloidal crystals by controlled centrifugation settling. Silica inverse opals were then prepared by using the colloidal crystals as templates and TEOS/ethanol solution. The inverse opals were infiltrated with Rhodamine 6G and laserlike emission was observed at 590 nm under 532 nm pump wavelength. The data show line narrowing of the dye fluorescence and a laser threshold of similar to 0.1 mJ/pulse. Local-field effects and light scattering due to structural defects are the main mechanisms contributing to generation of the laser-action observed. (c) 2005 Elsevier B.V. All rights reserved.